The Impact of Deliberative Strategy Dissociates ERP Components Related to Conflict Processing vs. Reinforcement Learning - Warren, Christopher M.; Holroyd, Clay B. (Frontiers in Neuroscience, 2012)
We applied the event-related brain potential (ERP) technique to investigate the involvement of two neuromodulatory systems in learning and decision making: The locus coeruleus-norepinephrine (LC-NE) system and the mesencephalic dopamine system (DA system). We have previously presented evidence that the N2, a negative deflection in the ERP elicited by task-relevant events that begins approximately 200 ms after onset of the eliciting stimulus and that is sensitive to low-probability events, is a manifestation of cortex-wide noradrenergic modulation recruited to facilitate the processing of unexpected stimuli (Warren, Tanaka, & Holroyd, in press). Further, Holroyd and Coles (2002) proposed that the impact of DA reinforcement learning signals on the anterior cingulate cortex (ACC) produces a component of the ERP called the feedback-related negativity (FRN). The N2 and the FRN share a similar time range, a similar topography, and similar antecedent conditions. We varied factors related to the degree of cognitive deliberation across a series of experiments to dissociate these two ERP components. Across four experiments we varied the demand for a deliberative strategy, from passively watching feedback, to more complex/challenging decision tasks. Consistent with our predictions, the FRN was largest in the experiment involving active learning and smallest in the experiment involving passive learning whereas the N2 exhibited the opposite effect. Within each experiment, when subjects attended to color, the N2 was maximal at frontal-central sites, and when they attended to sex it was maximal over lateral-occipital areas, whereas the topology of the FRN was frontal-central in both task conditions. We conclude that both the DA system and the LC-NE system act in concert when learning from rewards that vary in expectedness, but that the DA system is relatively more exercised when subjects are relatively more engaged by the learning task.